2011
DOI: 10.5761/atcs.oa.11.01663
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preoperative Short-term Intense Physical Therapy in Lung Cancer Patients:A Randomized Controlled Trial

Abstract: Background: We planned to investigate the effect of preoperative short period intensive physical therapy on lung functions, gas-exchange, and capacity of diffusion, and ventilation-perfusion distribution of patients with non-small cell lung cancer. Methods: Sixty patients with lung cancer, who were deemed operable, were randomly allocated into two groups. Intensive physical therapy was performed in patients in the study group before operation. Both groups received routine physical therapy after operation. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 12 publications
1
127
0
13
Order By: Relevance
“…Three studies did not specify the time frame of intervention implementation prior to treatment [16][17][18]. Standard care varied according to individual institutions whereby verbal or written instructions were given [15,[19][20][21], physical activity was delivered in the rehabilitation setting post-treatment [22,23], generic risk management and active mobilisation was given [18] or fast-track surgery was implemented [24]. Five studies delivered interventions in the pre-treatment period only [12,17,18,[25][26][27]; the remaining studies continued the interventions during or after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies did not specify the time frame of intervention implementation prior to treatment [16][17][18]. Standard care varied according to individual institutions whereby verbal or written instructions were given [15,[19][20][21], physical activity was delivered in the rehabilitation setting post-treatment [22,23], generic risk management and active mobilisation was given [18] or fast-track surgery was implemented [24]. Five studies delivered interventions in the pre-treatment period only [12,17,18,[25][26][27]; the remaining studies continued the interventions during or after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from three studies [12,17,22] were combined in a meta-analysis which indicated a significant benefit for presurgical pulmonary exercise versus usual care on the total number of days spent in the hospital among lung cancer patients (MD = − 4.20, 95% CI = − 5.45-− 2.95, I 2 = 0%) (see Fig. 3).…”
Section: Lung Cancer Pre-surgical Exercise Versus Usual Carementioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary rehabilitation, including exercise and education, is effective in candidates for lung volume reduction surgery, 19) and preoperative intensive physical therapy appears to be effective for surgical patients with lung cancer. 20) Inhalation therapy can improve exercise tolerability by decreasing hyperinflation of lungs, 21) and preoperative smoking cessation can also play a role. 22) ERS/ESTS guidelines recommend smoking cessation two to four weeks before surgery for lung cancer, 3) but 28.6% of patients continue to smoke within two weeks of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative respiratory physiotherapy following lung resection reduces respiratory complications in adult patients. 1,2 However, children have specific physiological differences, suggesting that their postoperative complications may differ from those of adults. 3,4 Children rarely undergo lung resection.…”
Section: Introductionmentioning
confidence: 99%